Le progrès technique chez Joan Robinson : un essai de systématisation et de formalisation - Heller, Claudia [UNESP] (CAIRN, 2001)
This paper deals with Joan Robinson's contributions to the issue of technical progress and her attempts of treating this subject in accordance to the Keynesian theory of employment and income distribution, mainly in the long run. This paper aims to review this aspect of her work and to establish a systematisation and a formalisation of her approach. At the same time the paper exposes the problems she faced - and did not always solve. Looking through her main contributions, the paper concludes that she used different criteria for the classification of innovations and that they depended on the specific situations described by the models in which she used the classification.
Technical progress in Joan Robinson's writings, an essay of systematisation and formalisation